The relationship between postnatal depression, sociodemographic factors, levels of partner support, and levels of physical activity - Saligheh, Maryam; Rooney, Rosanna M.; McNamara, Beverley; Kane, Robert T. (Frontiers in Psychology, 2014)
Background: postnatal depression (PND) is defined as a psychological mood disorder that occurs in a mother within six weeks of her giving birth. It refers to an episode that causes mood disturbance and it could begin in, or extend into, the postpartum period. It is thought to have a high impact upon the mother’s health as well as the family’s functioning and the child’s development. Socio-demographic, psych-social, and physical activity factors may all contribute to postpartum mood and ability to cope with responsibilities. The primary aim of this study was to determine which of these factors predicted PND in postpartum women. A secondary aim was to identify the socio-demographic and psycho-social predictors of physical activity in postpartum women . Methods: The study used a cross-sectional correlational design. A sample of 150 postpartum women was sent a package of six standardised questionnaires. Results: There was no association between physical activity and PND; however, older mothers, mothers of younger children, mothers who are less reluctant to ask for help, and mothers who are more satisfied with the help they get experience lower levels of PND. Mothers of older babies, mothers with more children, and less educated mothers are more likely to engage in caregiving activities, whereas mothers with fewer children and higher levels of partner support are more likely to engage in occupational activities. None of the socio-demographic factors or any of the parenting factors predicted levels of sporting activity.